Urgensi Pendidikan Manajemen pada Organisasi Kemahasiswaan di Institut Agama Islam Al-Hikmah Tuban - Tatang Aulia Rahman (Institut Agama Islam Al-Hikmah Tuban, 2022)
Management is an activity to organize and manage all things effectively and efficiently in order to achieve the expected goals. Therefore, management is a very important thing to do in this increasingly advanced and sophisticated world civilization. Student organizations in campus life are considered capable of becoming a forum for students to shape the character and personality of students. Besides being able to give its own color to the campus climate, the presence of student organizations is able to develop the potential and talents of students outside of academic activities so that they are ready to face the challenges of the times. Therefore, in carrying out the organizational process, it is necessary to add an understanding of how to manage and manage well so as to bring up new innovations and creativity in carrying out their duties as an organizational activist. Researchers used qualitative methods and case study approaches in this study. The data collection process was obtained from various relevant sources to be used as references. Organizations will provide more optimal benefits for students and institutions if the process uses good management. Currently, the implementation of student organizations at IAI Al Hikmah Tuban has used good management principles, but there are still some things that are still not optimal so that they must continue to be improved. Therefore, it is necessary to have high enthusiasm and consistency from every student in organizing so that it can have a positive impact on students and the development of the IAI Al Hikmah Tuban campus. Keywords: Management, Organization, Students